Age of menarche and final height in patients with permanent congenital hypothyroidism - Pegah Karimian; Silva Hovsepian; Tahereh Alinia; Homeyra Raispour; Naghmeh Mirshahzadeh; Mahin Hashemipour (Annals of Pediatric Endocrinology & Metabolism)
Purpose We compared the age at menarche and standard deviation score (SDS) of final height (FH) in permanent congenital hypothyroidism (CH) patients with those of healthy female adolescents and assessed their associations with CH screening-related variables or demographic factors. Methods In this cross-sectional study, we included 207 female CH patients and 598 healthy age-matched female adolescents. Ages at puberty onset and menarche, height at puberty and menarche, and the FH and its SDS were evaluated in the 2 groups and compared. Associations between screening variables and anthropometric data with age at menarche and SDS of FH were also assessed in CH patients. Results In the included population, 113 patients with CH and 453 healthy girls attained their FH. The mean ages at puberty onset and menarche in CH patients were higher than those in the healthy population (P<0.05). The mean height at menarche and the FH and its SDS were not different between the 2 groups (P>0.05). There was no significant association between FH SDS in CH patients and age of treatment (P=0.30). Age at menarche was significantly higher in CH patients with delayed age at treatment initiation (P=0.04). The difference between FH and target height was not significantly different among CH patients (P=0.83). Conclusions While CH patients had a significantly higher age at menarche compared to the healthy population, appropriate treatment changed this age to be similar to that in the healthy group. However, CH patients who experienced delayed treatment had a higher age at menarche. Age at treatment initiation was the only screening-related variable related to age at onset of menarche and puberty.